Inhibition of aspergillus niger by application of punica granatum peels and cucurbita maxima seeds as bio-fungicide / Sarina Mohamad … [et al.] - Mohamad, Sarina; Abd Hadi, Nur Atiqah; Azis, Tun Mohd Firdaus; Rahim, Nur Syafiqah (Faculty of Applied Sciences, 2020)
Infection on plant caused by Aspergillus niger leads to the destruction of quantity and quality of crop yields. Normally, this disease is solved by the chemical fungicides. Therefore, this study was carried out to seek a potential natural fungicide from fruit waste which is safer and economical to inhibit Aspergillus niger. Cucurbita maxima (pumpkin) seeds and Punica granatum (pomegaranate) peels were extracted using maceration method with 80 % ethanol. Brine Shrimp Lethality Assay (BLSA) was used to test the presence of bioactive components in the extracts at concentration of 10 µg/mL, 100 µg/mL and 1000 µg/mL and they are expressed in terms of LC50 (Median Lethal Concentration) respectively. The study revealed that Cucurbita maxima extract was inactive, while Punica granatum extract and the mixture of both extracts at ratio 1:1 were active at 1000 µg/mL. Furthermore, the antifungal activity of Cucurbita maxima extract, Punica granatum extract, and mixture of both extracts were further tested using well-diffusion method against A. niger at 25 mg/mL, 50 mg/mL, 75 mg/mL and 100 mg/mL respectively. The findings revealed the mixture of both extracts were exerted effectively against A. niger at the lowest concentration with 20.67±2.52 mm and this gave significant zone of inhibition. The result of the study indicates that the mixture extraction of pomegranate peels and pumpkin seeds at 25 mg/mL has a great potential to be formulated as commercial bio-fungicide.